The Werner syndrome RECQ helicase targets G4 DNA in human cells to modulate transcription. (16th March 2016) - Tang, Weiliang; Robles, Ana I.; Beyer, Richard P.; Gray, Lucas T.; Nguyen, Giang H.; Oshima, Junko; Maizels, Nancy; Harris, Curtis C.; Monnat, Raymond J.
Abstract : The Werner syndrome (WS) is a prototypic adult Mendelian progeroid syndrome in which signs of premature aging are associated with genomic instability and an elevated risk of cancer. The WRN RECQ helicase protein binds and unwinds G-quadruplex (G4) DNA substrates in vitro, and we identified significant enrichment in G4 sequence motifs at the transcription start site and 5′ ends of first introns (false discovery rate < 0.001) of genes down-regulated in WS patient fibroblasts. This finding provides strong evidence that WRN binds G4 DNA structures at many chromosomal sites to modulate gene expression. WRN appears to bind a distinct subpopulation of G4 motifs in human cells, when compared with the related Bloom syndrome RECQ helicase protein. Functional annotation of the genes and miRNAs altered in WS provided new insight into WS disease pathogenesis. WS patient fibroblasts displayed altered expression of multiple, mechanistically distinct, senescence-associated gene expression programs, with altered expression of disease-associated miRNAs, and dysregulation of canonical pathways that regulate cell signaling, genome stability and tumorigenesis. WS fibroblasts also displayed a highly statistically significant and distinct gene expression signature, with coordinate overexpression of nearly all of the cytoplasmic tRNA synthetases and associated ARS-interacting multifunctional protein genes. The 'non-canonical' functions of many of these upregulated tRNA charging proteins may together promote WS disease pathogenesis. Our results identify the human WRN RECQ protein as a G4 helicase that modulates gene expression in G4-dependent fashion at many chromosomal sites and provide several new and unexpected mechanistic insights into WS disease pathogenesis.